Development of "Tikrar Space" multimedia based on drill and practice for Arabic vocabulary learning - Nurhidayah, Siti; Fadhli, Muhibuddin; Ulfa, Saida (Jurnal Inovasi Teknologi Pendidikan, 2024)
Multimedia drill and practice is a learning method that teaches skills through structured exercises to students by integrating various types of media, such as text, images, sound, and video. It can be applied in learning Arabic, especially to increase interest in learning and understanding or also called mufrodat on the subject matter of "Ø§Ø¹Ø¶Ø§Ø¡ Ø§Ù„Ø¬Ø³Ù…" (Members of the Body) Class V which is located at SD Islamic Global School. This study involved 20 students as the subject of this development research is to produce products and determine the validity of a multimedia drill and practice named "Tikrar Space". This research was conducted through the stages of analysis (needs analysis, task analysis, and learning analysis), design (objectives and assessments, learning strategies, and selection of delivery systems), development (material drafts, media production, and formative evaluation), implementation, and summative evaluation according to the Seels and Glasgow development model. The validation test results showed that the material expert validation resulted in a percentage of 95% and the media expert validation resulted in a percentage of 98%. Then, the results of student trials using multimedia amounted to 93%. Based on these results, it is concluded that this product is valid and can be used to interact in learning.  Future research is suggested to integrate the latest technology with approaches such as gamification, adaptive learning, and collaborative learning, as well as the utilization of Augmented Reality and Virtual Reality to increase the effectiveness and interactivity of learning.